Winter warming effects on tundra shrub performance are species-specific and dependent on spring conditions - Krab, Eveline J.; Roennefarth, Jonas; Becher, Marina; Keuper, Frida; Klaminder, Jonatan; Blume-Werry, Gesche; Kreyling, Juergen; Makoto, Kobayashi; Milbau, Ann; Dorrepaal, Ellen (The Journal of ecology, 2018)
1. Climate change-driven increases in winter temperatures positively affect conditions for shrub growth in arctic tundra by decreasing plant frost damage and stimulation of nutrient availability. However, the extent to which shrubs may benefit from these conditions may be strongly dependent on the following spring climate. Species-specific differences in phenology and spring frost sensitivity likely affect shrub growth responses to warming. Additionally, effects of changes in winter and spring climate may differ over small spatial scales, as shrub growth may be dependent on natural variation in snow cover, shrub density and cryoturbation. 2. We investigated the effects of winter warming and altered spring climate on growing-season performance of three common and widespread shrub species in cryoturbated non-sorted circle arctic tundra. By insulating sparsely vegetated non-sorted circles and parts of the surrounding heath with additional snow or gardening fleeces, we created two climate change scenarios: snow addition increased soil temperatures in autumn and winter and delayed snowmelt timing without increasing spring temperatures, whereas fleeces increased soil temperature similarly in autumn and winter, but created warmer spring conditions without altering snowmelt timing. 3. Winter warming affected shrub performance, but the direction and magnitude were species-specific and dependent on spring conditions. Spring warming advanced, and later snowmelt delayed canopy green-up. The fleece treatment did not affect shoot growth and biomass in any shrub species despite decreasing leaf frost damage in Empetrum nigrum. Snow addition decreased frost damage and stimulated growth of Vaccinium vitis-idaea by c. 50%, while decreasing Betula nana growth (p < .1). All of these effects were consistent the mostly barren circles and surrounding heath. 4. Synthesis. In cryoturbated arctic tundra, growth of Vaccinium vitis-idaea may substantially increase when a thicker snow cover delays snowmelt, whereas in longer term, warmer winters and springs may favour E. nigrum instead. This may affect shrub community composition and cover, with potentially far-reaching effects on arctic ecosystem functioning via its effects on cryoturbation, carbon cycling and trophic cascading. Our results highlight the importance of disentangling effects of winter and spring climate change timing and nature, as spring conditions are a crucial factor in determining the impact of winter warming on plant performance.